2003
DOI: 10.1086/502210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic-Resistant Pathogens Colonizing the Respiratory Secretions of Patients in an Extended-Care Area of the Emergency Department

Abstract: Prolonged stay in the ED posed a risk for colonization with MROs and for contracting nosocomial infections, both of which were associated with increased mortality. Patients colonized with antibiotic-resistant A. baumannii may serve as a reservoir for spread in this hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…were the dominant MDR pathogens among the case patients. The mortality rate was significantly higher for the cases than for the controls (27% and 12.7%, respectively; P Ͻ 0.01), although susceptibility to carbapenems was allowed in the case group (16).…”
Section: Carbapenem-resistant Acinetobacter Sppmentioning
confidence: 89%
“…were the dominant MDR pathogens among the case patients. The mortality rate was significantly higher for the cases than for the controls (27% and 12.7%, respectively; P Ͻ 0.01), although susceptibility to carbapenems was allowed in the case group (16).…”
Section: Carbapenem-resistant Acinetobacter Sppmentioning
confidence: 89%
“…There are many benefits in avoiding unnecessary transfers to ED, for both the resident and healthcare services. As previously discussed, ED visits are associated with increased morbidity and mortality in older people . In addition, residents' utilise limited ED treatment space for extended periods waiting on investigations .…”
Section: Discussionmentioning
confidence: 99%
“…Another Brazilian study has found that patients colonized or infected with multidrug-resistant bacterial organisms had a higher length of stay than controls in the ER, and a higher associated mortality [27]. The presence of colonized patients in a chronically overcrowded and understaffed ER may represent another substantial obstacle to implementing hospital infection control measures [28], especially where resources are limited, and thus requiring specifically customized strategies.…”
Section: Discussionmentioning
confidence: 99%